An assessment of the contents of some heavy metals in Sri Lankan black tea (Camellia sinensis L.) and effect of oral administration of tea infusion in rats - Abeywickrama, K.R.W.; Amarakoon, A.M.T.; Ratnasooriya, W.D. (University of Colombo, 2010)
Hot water infusions (HWI) of black tea manufactured using fresh bud and tender leaves of Camellia sinensis L. (O) Kuntze ( Family: Theaceae) plant is a popular daily consumed beverage in Sri Lanka. Some heavy metals are inherently present in black tea. Ingestion of excessive amounts of these metals could cause health risk. Therefore, in this study, Copper, Mercury, Lead and Arsenic content of BOPF grade black tea, sampled from major agro-climatic elevations: low, mid and high grown in Sri Lanka and their HWI were determined using Atomic Absorption Spectrophotometer. The serum metal contents were assessed (using AAS) in rats orally administered with different doses of black tea HWI of high grown (human equivalent of 1.5, 3 and 12 cups per day), high dose (equivalent of 12 cups) of mid and low grown or water (control), thrice a day for consecutive 90 days. During the treatment, rats were daily observed for overt signs of toxicity and at the end of the treatment on chronic toxicity (renal and hepato-toxicity) were assessed. The total contents of heavy metals in black tea differ according to the agro-climatic elevations: Cu, 27.3 – 75.6 mg/kg; Hg, 0.01 – 0.026 mg/kg; Pb, 0.02 – 0.065 mg/kg and As, 0.003 – 0.006 mg/kg. The percent releases from black tea to their infusions were: Cu, 86 ± 8 %; Hg, 78 ± 6 %; Pb, 42 ± 3 % and As, 56 ± 9 %. Compared to control, blood serum metal contents were significantly (p < 0.05) and dose- dependently increased by black tea tested with high grown: Cu, 1.14 – 1.93 #g/dl; Hg, 0.10 – 0.19 #g/dl and Pb, 3.78 – 6.84 #g/dl. In contrast, As content was not altered (0.05 – 0.07 #g/dl). All metals tested were below the permissible limit prescribed by FAO. Further, there were no signs of toxicity. Therefore, daily consumption of even 12 cups of Sri Lankan black tea may not produce any health risk.